2017
DOI: 10.1016/j.chom.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus Tegument Protein UL82 Inhibits STING-Mediated Signaling to Evade Antiviral Immunity

Abstract: Recognition of human cytomegalovirus (HCMV) DNA by the cytosolic sensor cGAS initiates STING-dependent innate antiviral responses. HCMV can antagonize host immune responses to promote latency infection. However, it is unknown whether and how HCMV targets the cGAS-STING axis for immune evasion. Here we identified the HCMV tegument protein UL82 as a negative regulator of STING-dependent antiviral responses. UL82 interacted with STING and impaired STING-mediated signaling via two mechanisms. UL82 inhibited the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
156
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(173 citation statements)
references
References 54 publications
(70 reference statements)
9
156
0
Order By: Relevance
“…Consistent with the importance of MITA trafficking in antiviral response, recent studies show that iRhom2‐mediated MITA trafficking is antagonized by pathogenic viruses as an escape strategy with respect to antiviral responses . HCMV tegument protein UL82 inhibits the assembly of the MITA‐iRhom2‐TRAPβ complex, and impairs MITA trafficking from the ER to the Golgi apparatus and its recruitment of TBK1 and IRF3, leading to blockade of host antiviral immune responses . It is interesting to note that UL82 selectively inhibits iRhom2‐mediated trafficking but not the stability of MITA .…”
Section: Rhomboid‐like Pseudoproteases In Immune Evasionmentioning
confidence: 79%
See 1 more Smart Citation
“…Consistent with the importance of MITA trafficking in antiviral response, recent studies show that iRhom2‐mediated MITA trafficking is antagonized by pathogenic viruses as an escape strategy with respect to antiviral responses . HCMV tegument protein UL82 inhibits the assembly of the MITA‐iRhom2‐TRAPβ complex, and impairs MITA trafficking from the ER to the Golgi apparatus and its recruitment of TBK1 and IRF3, leading to blockade of host antiviral immune responses . It is interesting to note that UL82 selectively inhibits iRhom2‐mediated trafficking but not the stability of MITA .…”
Section: Rhomboid‐like Pseudoproteases In Immune Evasionmentioning
confidence: 79%
“…Previous studies demonstrate that the trafficking of MITA is essential for its activation and the recruitment of downstream TBK1 and IRF3, leading to the induction of type I IFNs and other antiviral proteins for efficient innate immune responses against viral invasion . Consistent with the importance of MITA trafficking in antiviral response, recent studies show that iRhom2‐mediated MITA trafficking is antagonized by pathogenic viruses as an escape strategy with respect to antiviral responses . HCMV tegument protein UL82 inhibits the assembly of the MITA‐iRhom2‐TRAPβ complex, and impairs MITA trafficking from the ER to the Golgi apparatus and its recruitment of TBK1 and IRF3, leading to blockade of host antiviral immune responses .…”
Section: Rhomboid‐like Pseudoproteases In Immune Evasionmentioning
confidence: 82%
“…Several viral proteins directly target STING trafficking to the ERGIC, which requires the iRhom2/TRAPb complex [54]. The HCMV tegument protein UL82 disrupts the complex between STING, iRhom2 and TRAPb [59]. Similarly, HCMV UL42, along with its role in antagonizing cGAS oligomerization, is reported to stimulate degradation of TRAPb in order to block STING trafficking [27].…”
Section: Pathogens Block Sting Signalosome Assemblymentioning
confidence: 99%
“…Similarly, the E2 proteins of HPV16 inhibit the transcription of different ISGs by targeting STING (Sunthamala et al, 2014). Another study has shown that both human and mouse cytomegalovirus (CMV) induce a cGAS/STING-dependent type I IFN response or actively inhibit STING through its UL82 tegument protein or US9 glycoprotein (Choi et al, 2018; Fu et al, 2017; Lio et al, 2016). Several studies have shown that some retroviruses including HIV, murine leukemia virus, and simian immunodeficiency virus can induce a type I IFN response due to recognition of reverse-transcribed DNA by cGAS and subsequent production of cGAMP (Gao et al, 2013a; Lahaye et al, 2013; Rasaiyaah et al, 2013).…”
Section: Intracellular Recognition Of Dnamentioning
confidence: 99%